Perkembangan Delik Penodaan Agama Di Indonesia: Perspektif Historis Konstitusional - Rossa Ilma Silfiah; Zulkarnain Zulkarnain (Widya Yuridika, 2022)
The blasphemy offense in Indonesia is a strategic offense to be discussed in detail, historically and constitutionally. In this case religion is protected by the state, and religion is a guideline in society, nation and state, so that the existence of religion becomes the spirit of the formation of this country. Religious life cannot be separated from the discussion of religious freedom which is part of human rights. Freedom of religion in Indonesia is based on the First Precept of Belief in the One Supreme God, where freedom is freedom based on the values of religion that live in Indonesia. One's religious freedom will be face to face with the religious rights of others, so it requires rules to maintain common order. These religions include Islam, Christianity, Catholicism, Hinduism, Buddhism, and Confucianism which have been mentioned in the explanation of the Presidential Decree Law No. 1/1965 on the abuse/blasphemy of religion, and submits Article 156a to be part of Article 156 of The Criminal Code. The research uses normative legal research methods with historical and case approaches. The essence of the blasphemy regulation is to regulate harmonious religious life. This article will discuss the state's protection of religion and religious life from a historical-constitutional perspective as well as cases of blasphemy against religion that have occurred. By knowing some of the cases that occurred, both blasphemy against religion in the form of hate speech and the destruction of houses of worship, it will be easy to analyze the causal factors and solutions that must be carried out by both the government and the community